Determinants of intention in buying health and life insurance / Mohammad Izat Azali and Muhammad Azim Zabmir - Azali, Mohammad Izat; Zabmir, Muhammad Azim (Faculty of Business and Management, 2015)
This research was conducted to carry out a study entitled “Determinants of Intention in Buying Health and Life Insurance”. The purpose of this study is to investigate the key factors which lead to the one’s intention in buying insurance. The four independent variables are knowledge, age, income level and social influence and followed by dependent variable are intention in buying health and life insurance. The sample size used for this study was 180. Data was obtained by using convenience sampling. The study seeks to examine the relationship between independent variables (knowledge, age, income level and social influence) and dependent variable (intention in buying health and life insurance), and to identify the factors that give impact towards intention in buying health and life insurance. Finding shows that, there is a one’s intention in buying insurance and all independent variables (knowledge, age, income level and social influence) show significant relationship with the dependent variable (intention in buying health and life insurance). The most influential factor variables on one’s intention in buying insurance are social influence at 0.301 (3.01%). Overall, researchers achieved to answer all objectives in the study.